The Design of Traffic Signals at Intersection (International Journal of Innovative Research in Engineering & Management, 2022)
The traffic volume at intersections has  been arising a problem which leads to accidents, conflicts  and congestions. An efficient traffic control at  intersections helps in reduction of delays of all vehicles  and the probability of crashes. The movement of vehicles  efficiency is increased by providing traffic signals,  roundabouts, channelized islands at an intersection.  Signal timing is most important if we use traffic signals in  which green time decides the efficiency of movement of  vehicles along with pedestrian walk timing. At an  intersection, traffic volume studies are done with the  movement and classification of vehicles along with the  geometric elements of the road. The video graphic  method is used to collect the volume of vehicles for every  15-minutes interval and converted into PCU units.  Webster’s and IRC code method are used for signal  design. Saturation flow, lost times and passenger car  units, width of the road are the significant parameters  used to optimize the signal timing in planning, design and  control of signalized intersection.
Keywords: PCU; roundabouts; channelized islands; saturation flow; optimization